THE CRIMINAL JUSTICE SYSTEM'S RESPONSE TO GAMBLING CRIME - Sahrul, Sahrul; Fahrurrozi, Fahrurrozi; Sarudi, Sarudi; Brilian, Giandika (Universitas Muhammadiyah Mataram, 2024)
Gambling in all its forms is contrary to religious, moral, and societal values, thus posing a threat to the nation and its interests. Gambling is defined as the act of placing a wager on the outcome of a game or event, with the expectation of improving the probability of a favorable result. This outcome is dependent on a number of factors, including chance, which distinguishes it from other forms of betting. Gambling is considered a deliberate criminal activity because those who engage in it are fully aware of the nature of their actions and the consequences they cause. The formulation of the problem is to identify the elements of the crime of gambling. This research is of the normative variety. The results of this study indicate that the elements of the crime of gambling are as follows: a) Game/race. The actions taken are usually in the form of a game or race. Therefore, it is conducted for the sake of leisure or to fill idle time, with the intention of providing entertainment for the mind. This is a reactive act. However, it is not necessary for the perpetrators to be directly involved in the game. They may simply be spectators or individuals who engage in betting on the course of a game or race.b) Fortune: The outcome of the game or race is more dependent on speculative elements, such as chance or luck, than on the skill or strategy of the players.c) In this game or competition, bets are placed by players or bookmakers. These can be in the form of money or other property, including wives. Due to the existence of bets, there are parties who benefit and are disadvantaged. This element is the most important in determining whether an action can be called gambling.